Keterbatasan Sumber Daya Manusia dalam Proses Produksi di PT PAL Indonesia: Tantangan dan Strategi Peningkatan Kinerja Organisasi - Anala Ilfi Xena Andini; Tutie Azzahra (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
PT PAL Indonesia faces a number of challenges in human resource management, one of which is that it prefers outsourcing orders rather than recruiting new qualified workers on the grounds that the company does not bear the cost of benefits. This limitation can have a direct impact on the efficiency and effectiveness of the production process, resulting in a decrease in company performance and becoming a serious obstacle in achieving optimal production goals. But on the other hand, there are several potential strategies to overcome the limitations of human resources at PT PAL Indonesia, such as developing employee training and development programs and improving communication between management and employees. To obtain accurate data in this research, the author used a qualitative approach by collecting data through in-depth interviews, observation, and document analysis. The results found in this study are that there is a need to improve the policies and practices of re-management at PT PAL Indonesia to improve their operational performance and competitiveness in the global market, provided that the recruitment carried out does show good quality towards the performance that will be carried out by employees.